Early Effects of Renal Replacement Therapy on Cardiovascular Comorbidity in Children With End-Stage Kidney Disease: Findings From the 4C-T Study. Issue 3 (March 2018) - Schmidt, Bernhard M.W.; Sugianto, Rizky Indrameikha; Thurn, Daniela; Azukaitis, Karolis; Bayazit, Aysun K.; Canpolat, Nur; Eroglu, Ayse Guler; Caliskan, Salim; Doyon, Anke; Duzova, Ali; Karagoz, Tevfik; Anarat, Ali; et al.
Abstract : Background: The early impact of renal transplantation on subclinical cardiovascular measures in pediatric patients has not been widely investigated. This analysis is performed for pediatric patients participating in the prospective cardiovascular comorbidity in children with chronic kidney disease study and focuses on the early effects of renal replacement therapy (RRT) modality on cardiovascular comorbidity in patients receiving a preemptive transplant or started on dialysis. Methods: We compared measures indicating subclinical cardiovascular organ damage (aortal pulse wave velocity, carotid intima media thickness, left ventricular mass index) and evaluated cardiovascular risk factors in 166 pediatric patients before and 6 to 18 months after start of RRT (n = 76 transplantation, n = 90 dialysis). Results: RRT modality had a significant impact on the change in arterial structure and function: compared to dialysis treatment, transplantation was independently associated with decreases in pulse wave velocity (ß = −0.67; P < 0.001) and intima media thickness (ß = −0.40; P = 0.008). Independent of RRT modality, an increase in pulse wave velocity was associated with an increase in diastolic blood pressure (ß = 0.31; P < 0.001). Increasing intima media thickness was associated with a larger increase in body mass index (ß = 0.26; P = 0.003) and the use of antihypertensive agents after RRT (ß = 0.41; P = 0.007). Changes in left ventricular mass index were associated with changes in systolic blood pressure (ß = 1.47; P = 0.01). Conclusions: In comparison with initiating dialysis, preemptive transplantation prevented further deterioration of the subclinical vascular organ damage early after transplantation. Classic cardiovascular risk factors, such as hypertension and obesity are of major importance for the development of cardiovascular organ damage after renal transplantation. Abstract : This analysis performed in pediatric kidney transplant recipients suggests that preemptive transplantation prevents deterioration of the subclinical vascular organ damage in comparison with initiating dialysis. Supplemental digital content is available in the text.